2015
DOI: 10.1016/j.ultsonch.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic cavitation erosion of high-velocity oxygen-fuel (HVOF) sprayed near-nanostructured WC–10Co–4Cr coating in NaCl solution

Abstract: The high-velocity oxygen-fuel (HVOF) spraying process was used to prepare near-nanostructured WC-10Co-4Cr coating. The cavitation erosion behavior and mechanism of the coating in 3.5 wt.% NaCl solution were analyzed in detail. The results showed that the amorphous phase and WC grain were present in the coating. The cavitation erosion resistance of the coating was about 1.27 times that of the stainless steel 1Cr18Ni9Ti under the same testing conditions. The effects of erosion time on the microstructural evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…According to the hard-sphere model, phase transformation is only half of the external stacking fracture energy. This transformation may absorb considerable amounts of impact energies from cavitation bubbles, resulting in the decrease of crack generation and propagation [30,31]. The phase transformation of the martensite in the material can be caused by the LSP itself [32].…”
Section: Resultsmentioning
confidence: 99%
“…According to the hard-sphere model, phase transformation is only half of the external stacking fracture energy. This transformation may absorb considerable amounts of impact energies from cavitation bubbles, resulting in the decrease of crack generation and propagation [30,31]. The phase transformation of the martensite in the material can be caused by the LSP itself [32].…”
Section: Resultsmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / u l t s o n Previously, a near-nanostructured WC-10Co-4Cr coating was synthesized successfully by HVOF spraying process and the microstructure, corrosion and cavitation erosion behavior in 3.5 wt.% NaCl solution was reported [14,15]. The results indicated that the main failure mechanism during cavitation erosion of the coating was erosion of the binder phases, brittle detachment of hard phases and formation of corrosion products.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Our previous studies [14,15] have shown that the near-nanostructured WC-10Co-4Cr coating was successfully prepared by HVOF spraying technology. The coating was composed of amorphous phase, nanoclusters and tungsten carbides, including W 2 C and WC.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Ding et al [16] observed that HVOF prepared nanostructured WC-12Co coating exhibits the excellent cavitation erosion resistance due to the dense microstructure, low porosity as well as high fracture toughness of the coating. According to Hong's study [17], porosity played a dominant role in cavitation erosion resistance of near-nanostructured WC-10Co-4Cr coatings deposited by HVOF. In addition, post-treatment methods optimized the microstructure of the coating for better performance.…”
Section: Introductionmentioning
confidence: 99%